MUTU PELAYANAN, MUTU PRODUK, DAN HARGA PENGARUHNYA TERHADAP LOYALITAS PELANGGAN - Irawati, Rina; Arifin, Zainul; Ziyad, Ilham Abdillah (Politeknik Negeri Ambon, 2025)
Introduction: Customer loyalty is a crucial factor in shaping customer attitudes toward a product, leading to a consistent and sustainable willingness to purchase it over other products. This study examines the relationship between service quality, service products and price to consumer loyalty in UD BS Makmur, Mojokerto. UD BS Makmur is a primary food supplier and is currently undertaking numerous management improvements to maintain its existence amidst intense competition. Methods: The research sample consisted of 60 consumers who used the Roscoe formula and the Accidental Sampling technique. Data analysis was conducted using descriptive statistics and Regression Analysis.Results: The results showed that service quality, product quality, and price significantly influenced customer loyalty; thus, all research hypotheses were accepted. Customers who are satisfied with better service and higher-quality products will make repeat purchases and recommend the company's excellent products to others. If a company's price meets customer expectations and customers perceive the benefits and value of the product, they will be more likely to be loyal to that company. The dominant independent variable was product quality (X2).Conclusion and suggestions: (1) Adding more modern machines, (2) Increasing the number of employees, (3) Providing digital payments, and (4) Ordering online via WhatsApp Business for a quick response Keywords: Service Quality, Product Quality, Price, Customer Loyalty